“I couldn't live without my factory now” The recruitment of women into the workforce in Communist Czechoslovakia in the 1950s - Nečasová, Denisa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
This paper provides a gender analysis of the recruitment campaigns aimed at bringing women into the workforce in Czechoslovakia in the 1950s. This period was noteworthy for the intensity of the recruitment campaigns and for the image of the female worker, which contrasted markedly with traditional ideas of femininity. In later years as the campaign lost its intensity the discourse construction more often reflected other images of the new socialist woman, particularly in terms of their private lives. Methodologically, this is a cultural-historical study based on gender analysis and critical discourse analysis. The sources are largely made up of periodicals from the time and instructional pamphlets for women, as well as archive material from the Central Committee of the Czechoslovak Communist Party and mass organizations for women.

Niniejsze opracowanie zawiera analizę płci kampanii rekrutacyjnych mających na celu wprowadzenie kobiet do szeregów siły roboczej w Czechosłowacji w latach 50. XX w. Okres ten był czasem szczególnej intensywności kampanii rekrutacyjnych i kreowania nowego wizerunku pracownicy, który wyraźnie kontrastował z tradycyjnymi ideami kobiecości. W późniejszych latach, gdy kampania straciła swoją intensywność, konstrukcja dyskursu częściej odzwierciedlała inne obrazy nowej socjalistycznej kobiety, szczególnie w sferze ich życia prywatnego. Metodologicznie zaproponowano w artykule badanie kulturowo-historyczne oparte na analizie płci i krytycznej analizie dyskursu. Materiał badawczy stanowią źródła zastane – czasopisma z epoki i broszury instruktażowe dla kobiet. Analizie poddano również materiały archiwalne z Komitetu Centralnego Czechosłowackiej Partii Komunistycznej i organizacji masowych dla kobiet.
This paper was made possible through the Support for Internationalization and Excellence in Publication Activities programme at the Faculty of Arts, Masaryk University.
Keywords: gender; Communism; Czechoslovakia; workforce; płeć; komunizm; Czechosłowacja; siła robocza